Manque í íªtre: Psychoanalysis in the Dilemma of Constructing Subject in Culture and Literature - Hari Murti, Ghanesya; Datau, Rizal Octofianto; Andang Subaharianto (Universitas Airlangga, 2023)
Psychoanalysis has been able to assert historically that it is not a closed branch of science to other disciplines. Its contribution to literature and culture makes it able to flexibly explain the dilemma of subject formation both in literature and culture. Freud, the founding father of psychology owes a debt to the Oedipus Rex story that anchors his entire thought. Acrobatically, Freud's thought was then continued by Lacan in order to explain cultural events that were born like language structure events. Language, literature, and culture then have a meeting point where the cultural process that is never final is precisely a signal that the subject always tries to overcome the shortcomings in himself when slaughtered by language. Language is unable to express itself fully, so literature and culture as products are nothing, but an extension of the subject who continues to feel lack. Zizek as the latest thinker from the previous two generations makes a foothold that the back and forth between the author and his work as an attempt to overcome the logic of deficiency or symptoms embodying the self and the fictional world in order to achieve wholeness exactly like the experience of returning to the mother's body or the real.